KECERDASAN EMOSIONAL (EMOTIONAL QUOTIENT) DALAM PENINGKATAN PRESTASI BELAJAR - Andriani, Asna (EDUKASI: Jurnal Pendidikan Islam, 2014)
During this time many people have an opinion that everyone needs an Intellectual Quotient (IQ) to reach an achievement in their live, but today according to a research product in psychology field gives an evidence that not only an Intellectual Quotient (IQ) but also there is the other factor which influences an achievement or a successful in the future. Its named an Emotional Quotient (EQ) which has means a personâs capability for managing and motivating his emotion, and interlacing the relationship with others. So that we can say that EQ is a foundation of reaching achievement for the student in their studying. This papper will discusse about the influence of Emotional Quotient (EQ) towards studentâs achievement in their live. There fore the parents, teachers, and counselors hopped to know and apply it for their sons, daughters, students, and cliens, in order that they can reach a good achievement in their school and more to be successful in their future.